1996
DOI: 10.1016/0370-2693(96)00483-2
|View full text |Cite
|
Sign up to set email alerts
|

A study on the rare radiative decay

Abstract: We study the decay B c → D * s γ. There are two mechanisms contributing to the process. One proceeds through the short distance b→sγ transition and the other occurs through weak annihilation accompanied by a photon emission. The electromagnetic penguin contribution is estimated by perturbative QCD and found to be 4.68 × 10 −18 GeV . In particular, we find the contribution of the weak annihilation is 6.25 × 10 −18 GeV which is in the same order as that of the electromagnetic penguin.The total decay rate Γ(B c →… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
(6 reference statements)
4
21
0
Order By: Relevance
“…(2.21)-(2.25) and shown in figures 6-13. In our calculation, if only Q 7 and Ann contributions are considered, we find that the relationship dBr [20][21][22], the same relationship also holds.…”
Section: Observables and Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…(2.21)-(2.25) and shown in figures 6-13. In our calculation, if only Q 7 and Ann contributions are considered, we find that the relationship dBr [20][21][22], the same relationship also holds.…”
Section: Observables and Discussionsupporting
confidence: 62%
“…[17][18][19] only the b → s(d)ll short-distance contribution is considered. Recently, using the annihilation form-factors of B c → D * s γ [20][21][22], the B c → D * s ll transitions combined with the annihilation effects have been analysed…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Ref. [2], the Wilson coefficient C eff 7γ is obtained neglecting the mixing of O 7γ with other operators, while in Ref. [1], this approximation is not employed.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…In the existing studies [1][2][3][4][5], the annihilation (Ann) and penguin (Peng) diagrams, as shown in Fig. 1, are paid attention to.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation